The development of persistent truant behaviour: an exploratory analysis of adolescents' perspectives. Issue 3 (3rd July 2017) - Keppens, Gil; Spruyt, Bram
Abstract: Background: While, an extensive literature reveals the many risk factors associated with truancy, less is known about the way truancy develops, intensifies and persists. In recent years, authors have argued that the development of truancy should not be understood as an individual phenomenon, but as a process of complex interactions between the adolescent and his/her parents, peers, teachers and school staff. There is, however, little research on how relationships between these parents, peers, teachers and school staff operate and influence the development of truancy. Purpose: In this paper, we try to fill this gap by analysing the narratives of truanting adolescents, and by investigating their experiences of the onset and persistence of their own truancy. Sample, design and methods: As part of a larger study, 20 adolescents from Flanders, the Dutch-speaking part of Belgium, were individually interviewed. Data were analysed qualitatively. Results and conclusions: The stories suggest that what begins as occasional truancy can easily evolve into persistent truancy that eventually could lead to permanent non-attendance. For many of the interviewed pupils, the development of their truancy can best be described as 'truant spirals'. Compared to the seemingly easy transition towards truanting for the first time, the narratives suggest that it is extremely difficult to curtail the pattern of persistent and intensifying truant behaviour.